Effects of Danhong Injection on platelet aggregation in hyperlipidemia rats. (15th February 2018) - Fan, Hongjing; Li, Min; Yu, Li; Jin, Weifeng; Yang, Jiehong; Zhang, Yuyan; Wan, Haitong
Abstract: Ethnopharmacological relevance: Danhong Injection (DHI), a Chinese medical product extracted from Radix et Rhizoma Salviae Miltiorrhizae ( Salvia miltiorrhiza Bge., Labiatae, Danshen in Chinese) and Flos Carthami ( Carthamus tinctorius L., Compositae, Honghua in Chinese), has been reported to have effects on inflammatory, anti-fibrinolytic properties, antithrombotic and decrease blood-lipid. It is extensively used for the clinical treatment of cardiovascular disease. This study aimed to investigate the effects of DHI on blood-lipid levels and platelet aggregation rate in hyperlipidemia rats. Materials and methods: Rats were randomly divided into 6 groups: normal control (NC), model control (MC), DHI-treated control at doses of 1.0 mL/kg, 2.0 mL/kg, 4.0 mL/kg, respectively, and Simvastatin positive control at dose of 2.0 mg/kg. All DHI treated groups were intraperitoneally injected for 7 days. The effects of DHI on serum triglyceride (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C) were evaluated. And platelet activating factor (PAF), platelet membrane glycoprotein IIb/IIIa (GP IIb/IIIa) and 6-keto-prostaglandin F1а (6-K-PGF1а) were determined by enzyme-linked immunosorbent assay (ELISA). Moreover, the expression of prostaglandin I-2 (PGI2 ), prostaglandin E-2 (PGE2 ) and thromboxane A2 (TXA2 ) in liver was determined by real-time PCR. Results: Compared with the MC group, the rats treated with DHI had significantly reduced TC, TG, LDL-C, FIB, GP IIb/IIIa and platelet aggregation. Meanwhile, the thrombin time (TT), activated partial thrombin time (APTT), prothrombin time (PT), 6-K-PGF1а was significantly increased. Expression of PGI2 and PGE2 mRNA was significantly increased, whereas the TXA2 was significantly reduced. Conclusions: This study demonstrated that the blood lipid and platelet aggregation has a regulatory effect after DHI treatment. The insights gained from this study will improve understanding of the mechanisms involved in the effect of DHI on hyperlipidemia and the pharmacological rationale for the use of DHI in diseases caused by formation of thrombosis and lipid metabolic disorders. Graphical abstract: